The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/jcm8030325
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effectiveness of Lornoxicam and Flurbiprofen on Management of Pain and Sequelae Following Third Molar Surgery: A Randomized, Controlled, Clinical Trial

Abstract: The aim of this study was to analyze the effectiveness of Lornoxicam and Flurbiprofen in reducing perioperative sequelae after impacted mandibular third molar surgery. Ninety-one patients who needed surgical extraction of an impacted mandibular third molar were selected for the study. All subjects were randomly allocated to receive one of the following treatments twice a day for 5 days after surgery: placebo (n = 29), Flurbiprofen (n = 31), or Lornoxicam (n = 31). The primary outcome was postoperative pain, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 32 publications
0
30
1
2
Order By: Relevance
“…After that, it is common to observe the decrease of the expected postoperative complications resulting in a significant improvement of the quality of life 13 . Accordingly, many clinicians [13][14][15][16] have emphasized the necessity for better control of pain, swelling, and trismus in patients who undergo third molar surgery. The use of local or systemic corticosteroids and nonsteroidal anti-inflammatory drugs is often recommended.…”
Section: Discussionmentioning
confidence: 99%
“…After that, it is common to observe the decrease of the expected postoperative complications resulting in a significant improvement of the quality of life 13 . Accordingly, many clinicians [13][14][15][16] have emphasized the necessity for better control of pain, swelling, and trismus in patients who undergo third molar surgery. The use of local or systemic corticosteroids and nonsteroidal anti-inflammatory drugs is often recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Isola et al, used Lornoxicam, Flurbiprofen and placebo for pain control after impacted third molar surgery, in their study. They reported that the peak pain level in the flurbiprofen group was 12 hours 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Isola et al, evaluated the efficacy of Lornoxicam, Flurbiprofen and Placebo on pain and edema after impacted third molar surgery and found that flurbiprofen was less effective than lornoxicam in the first 24 hours on pain, however, reported that all medicine group was equally effective on edema 18 . In our study, systemic and topical flurbiprofen form was used for postoperative pain and edema control after the third molar surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As an explanation of the results of the present study, it should be highlighted that the dysfunctional damage at the endothelium level found in patients with periodontitis and with CVD can be determined by a specific inflammatory and immune pathway in which MPO modulates a response towards pathogenic bacteria of the oral biofilm which are exacerbated during the active phases of periodontal damage. It has also been shown that MPO, during periodontal disease, mediates the immune response at the endothelial level through specific heat shock proteins which has been shown to be useful for stimulating the production of cross-reactive T cells [47][48][49][50][51][52]. In this regard, this process which sees MPO as a key modulator [53][54][55][56][57][58], has also been shown to influence the host defense mechanism that determines a subsequent activation of endothelial cell production [55,[58][59][60][61][62][63] which leads to an increased risk of future tissue damage effects due to periodontal pathogens bacteria in several oral diseases [43,[64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%